Organic polymer carrier, Z-N catalyst and preparation method and application thereof
By using a porous organic support supported Z-N catalyst prepared by copolymerizing divinylbenzene with unsaturated diester-based silane monomers, the problems of insufficient catalyst activity and easy support separation in the prior art are solved, and effective preparation of high molecular weight polyethylene and good catalyst activity are achieved.
Patent Information
- Application Number
- CN202311160070.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-08
AI Technical Summary
In the prior art, when preparing ultra-high molecular weight polyethylene (UHMWPE) catalysts, the catalyst activity is insufficient, resulting in insufficient molecular weight of the polymer, and the carrier is prone to detachment, resulting in uneven distribution of polymer particles.
A porous organic polymer support obtained by copolymerizing divinylbenzene with unsaturated diester-based silane monomer was used to carry a Z-N catalyst, and a catalyst with a good ethylene chain growth rate was integrated design and prepared by supporting magnesium and titanium metal.
Polymerization was achieved to obtain ultra-high molecular weight polyethylene with a viscosity average molecular weight of more than 7 million. The catalyst activity was significantly improved, the polymerization activity was good, and the support structure was stable, avoiding the problem of uneven distribution of polymerized particles.
Smart Images

Figure CN119591771A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalysts, and specifically relates to an organic polymer carrier, a ZN catalyst, a preparation method and application thereof, and particularly relates to an organic carrier-loaded ZN type ultra-high molecular weight polyethylene catalyst system and a preparation method thereof. Background Art
[0002] Ultra-high molecular weight polyethylene (UHMWPE) generally refers to linear long-chain polyethylene materials with a relative molecular weight of more than 1.5 million (or a viscosity-average molecular weight of 1 million). Ultra-high molecular weight polyethylene has excellent properties such as high strength, impact resistance, wear resistance, self-lubrication, chemical corrosion resistance, and low temperature resistance. The main products include fibers, films, pipes, plates, rods, porous materials and special-shaped materials, etc., which are widely used in aerospace, marine engineering, petrochemicals, new energy materials and other fields.
[0003] At present, the catalysts for preparing UHMWPE mainly include Ziegler-Natta catalysts, metallocene catalysts and non-metallocene catalysts, such as phenoxyimine (FI) catalysts. Ultra-high molecular weight polyethylene was first successfully developed using Ziegler-Natta catalysts (hereinafter referred to as "ZN catalysts"). There are many public methods for preparing ZN ultra-high molecular weight polyethylene catalysts. Usually, TiCl4 is loaded on compounds such as Mg(OR)2, MgCl2 or MgR2, and then various processes are used to prepare UHMWPE catalysts using alkyl aluminum reduction. In the process, internal electron donors can be added to regulate the electrophilicity of the Ti active center to control the catalyst performance, such as patents US4,447,587, US4,933,393 and US6,114,271. The molecular weight of the polymer can be adjusted by the amount of alcohol added, such as US4,138,540. In addition, US4,962,167 prepares a UHMWPE catalyst by reacting MgCl2 with an alkoxy titanium compound and then with aluminum trihalide and tetraalkoxysilane; in CN106220768A, an organosilicon compound electron donor is added to the Ti / Mg system of the UHMWPE catalyst; CN103509140A discloses a method for preparing an ultra-high molecular weight polyethylene catalyst, wherein an alcoholate is added to a solution after a magnesium halide compound carrier reacts with a hydrocarbon solvent to form an alcohol magnesium compound with the magnesium halide, and then a haloalkyl aluminum compound is added. The haloalkyl aluminum compound and the alcohol magnesium compound form an intermediate product, which is emulsified and then a titanium compound is added to carry out a titanium-supporting reaction, and the catalyst is obtained by washing and drying. The invention uses emulsification technology to not only greatly improve the catalyst activity, but also the resin obtained by polymerization has a higher viscosity-average molecular weight, which can reach more than 4 million. CN114181334A discloses an ultra-high molecular weight polyethylene catalyst system and a preparation method thereof. The catalyst components include a magnesium complex, an acetate compound, a titanium-containing compound, and at least one 1,3-diether electron donor and / or o-phenylenedimethyl ether electron donor. Olefin polymerization can obtain an ultra-high molecular weight polyethylene with a viscosity-average molecular weight greater than 7 million.
[0004] Metallocene catalysts and non-metallocene catalysts are single-active-center catalysts. Compared with ZN catalysts, they can produce polymers with narrower molecular weight distribution and improve product performance. Subsequently, multiple research teams and companies conducted research on metallocene catalysts. For example, Ticona used bridged metallocene catalysts to prepare ultra-high molecular weight polyethylene with a viscosity-average molecular weight greater than 1 million. Angew Chem Int Ed. "Donor-acceptor metallocene catalysts for the production of UHMWPE: Pushing the selectivity for chain growth to its limits" (2006; Vol. 45, pp. 1799-1803) uses [(Flu)Et2PB(Ph)2(Cp)]ZrCl2 metallocene compounds to prepare ultra-high molecular weight polyethylene with a viscosity-average molecular weight of 3.9 million. CN101356199A discloses a bis-indenyl-substituted bridged metallocene catalyst for ultra-high molecular weight polymers. The bridged metallocene catalyst can be dimethylsilylene-[2-isopropyl-4-(p-isopropyl-phenyl)indenyl][2-methyl-4-(p-isopropylphenyl)indenyl]zirconium dichloride, dimethylsilyl-bis(2-isopropylindenyl)zirconium dichloride, etc. The molecular weight of the metallocene catalysts currently reported for ultra-high molecular weight polyethylene is lower than that of ZN catalysts, and the synthesis of catalyst compounds is complex, and the catalyst and co-catalyst are expensive, which limits their industrial application.
[0005] At the same time, non-metallocene catalysts are also developing. CN102030844B discloses a supported non-metallocene polyolefin catalyst, which can be used to prepare ultra-low branching ultra-high molecular weight polyethylene, and the catalyst is a non-metallocene compound containing [ONX] tridentate ligand. Typical non-metallocene catalysts such as phenoxyimine (FI) catalysts can usually regulate the molecular weight of ultra-high molecular weight polyethylene by substituents on the compound. CN107936164A discloses a copolymerization type UHMWPE, which has a molecular weight comparable to that of a homopolymerization product, and also has a considerable comonomer content, and the comonomer content is adjustable and controllable, the particle morphology is good, the bulk density is high, the activity decay is not obvious, and alpha-olefin homopolymerization can be catalyzed without adding an internal electron donor and an external electron donor, and the wear resistance and impact strength performance loss of UHMWPE are relatively low. However, the supported non-metallocene catalyst is easy to break away during the polymerization process, resulting in uneven distribution of polymerized particles and the problem of sticking to the reactor.
[0006] Organic polymer carriers are different from reported inorganic carriers. POP carriers themselves will not introduce impurities, thus affecting the performance of polymers. In addition, organic carriers have the characteristics of controllable pore structure, high specific surface area, stable thermal performance, and easy functionalization. Through the design and functionalization of the carrier, high-performance or characteristic polyolefin catalysts can be prepared. There are public reports on porous organic carrier-supported ZN catalysts. Organic carriers containing functional groups such as carboxylic acid, hydroxyl, cyano, and amino groups are usually used to prepare ZN catalysts. The molecular weight of the polyethylene product obtained by polymerization is usually less than 300,000. For example, in "Porouspolyethylene spheres with nanofiber structure from Ziegler-Natta catalystsupported on porous polymer particles" (2011; Vol. 52, pp. 602-605), a POP carrier-supported ZN polyethylene catalyst was prepared using a cyano-functionalized organic carrier, and its weight-average molecular weight was between 100,000-200,000 g / mol. In "Ethylene polymerization on polymer supported Ziegler-Natta catalyst" (2012; 19: 9892, pp. 1-13), the weight average molecular weight of the ZN polyethylene catalyst prepared by using a POP carrier functionalized with methyl methacrylate is between 200,000 and 300,000 g / mol. In addition, metallocene catalysts prepared by using organic carriers, such as US 5,587,439, using organic carriers containing carboxylic acid ester groups to prepare metallocene catalysts, the molecular weight of the polyethylene product obtained by ethylene polymerization is less than 300,000. In addition, “Ultrahigh Molecular Weight Polyethylene Produced by a Bis(phenoxy-imine)Titanium Complex Supported on Latex Particles” in Journal of Polymer Science: Part A: Polymer Chemistry (2006; pages 3103-3113) adopts microemulsion polymerization to prepare a porous organic carrier containing pyridine functions and polyethylene oxide groups, and loads a bisphenolamine titanium (FI-Ti) catalyst compound to obtain an ultrahigh molecular weight polyethylene catalyst. The weight average molecular weight of the prepared polyethylene is between 2,000,000 and 7,000,000, and the active center of the ultrahigh molecular weight polyethylene catalyst belongs to the FI-titanium series, rather than the ZN catalyst.Patent US4,623,707 uses an organic support prepared from chloromethylated styrene monomer to prepare a ZN catalyst; Catalyst Letter "Immobilization of TitaniumTetrachloride on Mixed Support of MgCl2xEB / Poly(methyl acrylate-co-1-octene):Catalyst for Synthesis of Broad MWD Polyethylene" (2009; 132; 87-93) uses methacrylic acid and 1-octene copolymer as a support to prepare a ZN catalyst for the preparation of polyethylene with a wide molecular weight distribution. Summary of the invention
[0007] In order to solve the above problems, the purpose of the present invention is to provide an organic polymer carrier, a ZN catalyst and a preparation method and application thereof. The catalyst has good polymerization activity and can catalyze polymerization to obtain ultra-high molecular weight polyethylene with a viscosity-average molecular weight of more than 7 million.
[0008] In order to achieve the above object, the present invention provides an organic polymer carrier, which is obtained by copolymerizing monomers including divinylbenzene and unsaturated diester silane monomers; wherein the unsaturated diester silane monomer has a structure shown in Formula I:
[0009]
[0010] In formula I, R1, R2, and R3 are each independently selected from hydrogen, chlorine, bromine, C1-C6 straight-chain alkyl and derivatives thereof, C1-C6 branched-chain alkyl and derivatives thereof, cycloalkyl and derivatives thereof, and aromatic groups and derivatives thereof; x is 0-6; R4 is selected from hydrogen, C1-C8 straight-chain alkyl and derivatives thereof, C1-C8 branched-chain alkyl and derivatives thereof, cycloalkyl and derivatives thereof, and aromatic groups and derivatives thereof; R5 and R6 are each independently selected from hydrogen, C1-C8 straight-chain hydrocarbon groups and derivatives thereof, C1-C8 branched-chain hydrocarbon groups and derivatives thereof, cycloalkyl and derivatives thereof, and aromatic groups and derivatives thereof.
[0011] According to a specific embodiment of the present invention, preferably, in formula I, R1, R2, and R3 are each independently selected from hydrogen, ethyl, chlorine, bromine, and methyl; R4 is selected from methyl, ethyl, isopropyl, n-butyl, isobutyl, phenyl, phenoxy, methoxy, and ethoxy; R5 and R6 are each independently selected from hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, n-pentyl, n-heptyl, phenyl, cyclohexyl, isohexyl, 2-ethylpentyl, and 2-ethylbutyl; and x is 0 or 1.
[0012] According to a specific embodiment of the present invention, preferably, the unsaturated diester silane monomer is selected from vinylmethylbis(methylformate)silane, vinylmethylbis(methylacetate)silane (or vinylmethylbis(acetoxymethyl)silane), vinylmethylbis(methylpropionate)silane, vinylmethylbis(methylbutyrate)silane, vinylmethylbis(methylisobutyrate)silane, vinylmethylbis(methylvalerate)silane, vinylmethylbis(methylhexanoate)silane, vinylmethylbis(methyloctanoate)silane, vinylmethylbis(methyl2-methylhexanoate)silane, Vinylmethylbis(2-ethylhexanoate)silane, vinylmethylbis(2-ethylpentanoate)silane, vinylmethylbis(methylbenzoate)silane, vinylmethylbis(methylcyclohexanecarboxylate)silane, vinylethylbis(methyl acetate)silane, vinylphenylbis(methyl acetate)silane, vinyl n-butylbis(methyl acetate)silane, vinyl isobutylbis(methyl acetate)silane, vinyl isopropylbis(methyl acetate)silane, vinylethoxybis(methyl acetate)silane, allylmethylbis(methyl acetate)silane, allylmethylbis(methyl propionate) Silane, allylmethylbis(methyl n-butyrate)silane, allylmethylbis(methyl isobutyrate)silane, allylmethylbis(methyl n-pentanoate)silane, allylmethylbis(methyl n-hexanoate)silane, allylmethylbis(methyl n-octanoate)silane, allylmethylbis(methyl 2-methylhexanoate)silane, allylmethylbis(methyl 2-ethylhexanoate)silane, allylmethylbis(methyl 2-ethylpentanoate)silane, allylmethylbis(methyl benzoate)silane, allylmethylbis(methyl cyclohexane)silane, allylethylbis(methyl acetate)silane, allylphenyl One or a combination of two or more of di(methyl acetate)silane, allyl n-butyldi(methyl acetate)silane, allyl isobutyldi(methyl acetate)silane, allyl isopropyldi(methyl acetate)silane, allyl methoxydi(methyl acetate)silane, allyl ethoxydi(methyl acetate)silane, allyl ethoxydi(methyl benzoate)silane, 1-butenyl ethoxydi(methyl acetate)silane, 1-buten-4-yl isopropyldi(methyl benzoate)silane, allyl phenoxydi(methyl acetate)silane, and 1-chloroallyl ethoxydi(methyl acetate)silane.
[0013] According to a specific embodiment of the present invention, preferably, the mass fraction of the unsaturated diester silane monomer is 10-60% based on the mass of the organic polymer carrier as 100%; the content of the functional monomer in the carrier is determined by the added amount of divinylbenzene and the unsaturated diester silane functional monomer.
[0014] The present invention also provides a method for preparing the above-mentioned organic polymer carrier, which comprises the following steps: using monomers including the divinylbenzene, the unsaturated diester silane monomer and the additional monomer as raw materials, and obtaining the organic polymer carrier through copolymerization; the mass ratio of the additional monomer to divinylbenzene is 0-1:1; the mass ratio of the unsaturated diester silane monomer to divinylbenzene is 0.2-2:1.
[0015] According to a specific embodiment of the present invention, preferably, the organic polymer carrier is prepared by dispersion polymerization, suspension polymerization or emulsion polymerization.
[0016] According to a specific embodiment of the present invention, preferably, the organic polymer carrier is prepared by the dispersion polymerization method, which includes the following steps: adding divinylbenzene, unsaturated diester silane monomers, additional monomers, and then adding stabilizers and initiators to a dispersion solvent, stirring and dispersing, and reacting at 50-80°C for 5-12 hours to obtain the organic polymer carrier, which is recorded as POP-Si(CH2O2C)2; more preferably, the obtained organic polymer carrier can be further washed with a dispersion solvent to remove impurities and dried; the obtained organic carrier has narrow dispersion and good fluidity.
[0017] According to a specific embodiment of the present invention, preferably, in the above preparation method, the additional monomer includes one or a combination of two or more of styrene, alkyl-substituted styrene, chloromethyl-substituted styrene, methacrylic acid, methacrylate, and hydroxyalkyl methacrylate, such as hydroxyethyl methacrylate.
[0018] According to a specific embodiment of the present invention, preferably, in the above preparation method, the dispersing solvent includes a fatty acid ester solvent.
[0019] According to a specific embodiment of the present invention, preferably, the fatty acid ester solvent includes ethyl acetate and / or butyl acetate.
[0020] According to a specific embodiment of the present invention, preferably, in the above preparation method, the mass ratio of the total amount of monomer added to the dispersion solvent is 1:5-20, so that the system is evenly dispersed.
[0021] According to a specific embodiment of the present invention, preferably, in the above preparation method, the stabilizer is polyvinyl alcohol and / or polypropylene oxide-polyethylene oxide copolymer.
[0022] According to a specific embodiment of the present invention, preferably, the weight average molecular weight of the stabilizer is 1,000-100,000.
[0023] According to a specific embodiment of the present invention, preferably, the mass ratio of the amount of the stabilizer added to the total amount of the monomers added is 0.5-5:100.
[0024] According to a specific embodiment of the present invention, preferably, in the above preparation method, the initiator is azobisisobutyronitrile (AIBN) and / or dibenzoyl peroxide (BPO).
[0025] According to a specific embodiment of the present invention, preferably, the mass ratio of the amount of the initiator added to the total amount of the monomers added is 0.5-5:100.
[0026] According to a specific embodiment of the present invention, preferably, in the above preparation method, the divinylbenzene is pretreated divinylbenzene, and the pretreatment is to remove the polymerization inhibitor.
[0027] The present invention also provides a ZN catalyst, which, based on 100% by mass of the ZN catalyst, comprises 60-85wt% of an organic polymer carrier, 1-6wt% of a magnesium compound calculated as magnesium, 1-6wt% of a titanium compound calculated as titanium and 0-5wt% of an internal electron donor.
[0028] According to a specific embodiment of the present invention, preferably, the content of the organic polymer carrier is 65-80wt%, the content of the magnesium element is 2-5wt%, and the content of the titanium element is 2-5wt%.
[0029] According to a specific embodiment of the present invention, preferably, the magnesium compound is R n MgX (2 -n), n is 0, 1 or 2; R is selected from C1-C8 alkyl and its derivatives, aryl and its derivatives, alkoxy and its derivatives, and X is fluorine, chlorine, bromine or iodine.
[0030] According to a specific embodiment of the present invention, preferably, R is selected from methyl, ethyl, propyl, butyl, alkoxy, phenyl, and substituted phenyl.
[0031] According to a specific embodiment of the present invention, preferably, the magnesium compound is one or a combination of two or more of an alkyl magnesium halide compound, an alkyl magnesium compound, and an alkoxy magnesium halide compound, and more preferably an alkyl magnesium chloride compound.
[0032] According to a specific embodiment of the present invention, preferably, the magnesium compound includes one or a combination of two or more of methylmagnesium chloride, n-butylmagnesium chloride, isobutylmagnesium chloride, tert-butylmagnesium chloride, benzylmagnesium chloride, ethylmagnesium chloride, methylmagnesium bromide, ethylmagnesium bromide, n-butylmagnesium bromide, benzylmagnesium bromide, methylmagnesium iodide, tert-butylmagnesium iodide, benzylmagnesium iodide, n-butylmagnesium iodide, methylmagnesium fluoride, tert-butylmagnesium fluoride, diethylmagnesium, dipropylmagnesium, dibutylmagnesium, and ethoxymagnesium chloride; after the magnesium compound is contacted with the organic polymer carrier, a porous organic carrier treated with a magnesium compound is prepared, which is recorded as POP-Si(CH2O2C)2...MgX.
[0033] According to a specific embodiment of the present invention, preferably, the titanium compound is titanium tetrachloride; the porous organic support treated with the above-mentioned magnesium compound (POP-Si(CH2O2C)2...MgX) is further reacted with titanium tetrachloride to obtain the ZN catalyst, which is recorded as POP-Si(CH2O2C)2...MgX / TiCl4.
[0034] The ZN catalyst of the present invention can selectively add an additional internal electron donor (ID), and the obtained ultra-high molecular weight polyethylene catalyst solid component is recorded as POP-Si(CH2O2C)2...MgX / TiCl4 / ID; according to a specific embodiment of the present invention, preferably, the internal electron donor is one or a combination of two or more of a diester compound, a diphenol ester compound, a diol ester compound, a succinate compound, and a diether compound. The organic polymer carrier-supported ZN type UHMWPE catalyst solid catalyst component of the present invention has a good ethylene chain growth rate through the POP-Si(CH2O2C)2 group on its organic carrier and the additionally added (optionally added) internal electron donor.
[0035] According to a specific embodiment of the present invention, preferably, the internal electron donor includes one or a combination of two or more of diisobutyl phthalate (DIBP), di-n-butyl phthalate (DNBP), 9,9-dimethoxyfluorene, 2,3-diisobutyl diisopropylsuccinate, 3-methyl-5-tert-butyl-1,2-benzenediol dibenzoate, 2-isopropyl-2-isopentyl-1,3-propanediol dibenzyl ester (IAIPPDB), and 2-isopropyl-2-isopentyl-1,3-propanedimethyl ether (IAIPDMP).
[0036] The present invention also provides a method for preparing the above ZN catalyst, which comprises the following steps:
[0037] Under anhydrous and oxygen-free conditions, the organic polymer carrier is added to an inert solvent, the magnesium compound is added, and the reaction is carried out at 0°C-50°C for 15-120 minutes. The unreacted magnesium compound is filtered, and then an inert solvent and titanium tetrachloride are added. After reacting at 0°C-80°C for 15-180 minutes, an internal electron donor is added at 20°C-120°C, the reaction is carried out for 15-180 minutes, the reaction is filtered, and finally the ZN catalyst is washed with an inert solvent.
[0038] In the ZN catalyst of the present invention, the functional monomer content of the organic polymer carrier is generally 0.5 mmol / gram carrier to 5 mmol / gram carrier, preferably 1 mmol / gram carrier to 4 mmol / gram carrier. The functional monomer content is usually regulated by the ratio of the functional monomer to the divinylbenzene (DVB) monomer addition during the carrier preparation process. The amount of magnesium compound reagent added (in moles of magnesium Mg) and the amount of the carrier are 1 mmol / gram carrier to 30 mmol / gram carrier, preferably 3 mmol / gram carrier to 20 mmol / gram carrier. Usually, an excess of Ti metal compound is added, such as TiCl4, to load the catalyst, and the amount of Ti metal compound added (in moles of titanium Ti) is generally 5 mmol / gram carrier to 200 mmol / gram carrier, preferably 50 mmol / gram carrier to 150 mmol / gram carrier. The amount ratio of the internal electron donor to the carrier is 0 to 0.3 grams of internal electron donor / gram carrier.
[0039] The present invention also provides a ZN catalyst system, which comprises a ZN catalyst and a co-catalyst.
[0040] According to a specific embodiment of the present invention, preferably, the co-catalyst comprises an alkyl aluminum compound.
[0041] According to a specific embodiment of the present invention, preferably, the co-catalyst is triethylaluminum and / or triisobutylaluminum (TIBA); in addition, alkylaluminum compounds can also be used as impurity removers for the polymerization reaction system.
[0042] According to a specific embodiment of the present invention, preferably, the molar ratio of aluminum in the alkyl aluminum compound to titanium in the ZN catalyst is 10-500.
[0043] The present invention also provides application of the ZN catalyst or the ZN catalyst system in olefin polymerization.
[0044] According to a specific embodiment of the present invention, preferably, the olefin polymerization is ethylene homopolymerization.
[0045] According to a specific embodiment of the present invention, preferably, the olefin polymerization is gas phase polymerization, bulk polymerization or slurry polymerization.
[0046] According to a specific embodiment of the present invention, preferably, the reaction temperature of the slurry polymerization is 30-80°C, and the reaction pressure is 0.1-2.0Mpa.
[0047] According to a specific embodiment of the present invention, preferably, the solvent for the slurry polymerization is C5-C 10 An alkane, more preferably hexane.
[0048] The organic polymer carrier-supported ZN-type UHMWPE catalyst of the present invention adjusts the prepared carrier pore structure and morphology by screening out free radical polymerizable unsaturated diester silane functional monomers, and regulates the microchemical environment of the metal active center by relying on the diester silane functional groups on the carrier to prepare a POP-Si(CH2O2C)2 carrier. By loading magnesium and titanium metals, an organic carrier-supported POP-Si(CH2O2C)2 / RMgX / TiCl4 ultra-high molecular weight polyethylene catalyst solid component is integratedly designed and prepared. The diester silane functional groups on the carrier and the internal electron donor that can be added later can regulate the catalyst metal active center, reduce the chain transfer ability of the active center, and make the catalyst have good ethylene insertion ability and good polymerization activity. The ultra-high molecular weight polyethylene product can be obtained by catalyzing ethylene polymerization, and its relative molecular weight Mw reaches 10 million or the viscosity average molecular weight reaches more than 7 million. DETAILED DESCRIPTION
[0049] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0050] The comonomer divinylbenzene (DVB) used in the present invention can be a commercially available monomer with a DVB content of 55% or 80%. The monomer needs to be pretreated before use to remove the polymerization inhibitor. There are many methods for removing the polymerization inhibitor in the prior art. For example, divinylbenzene and styrene can be washed with NaOH solution and distilled water; the third monomer (additional monomer) such as hydroxyethyl methacrylate can be used to remove the polymerization inhibitor using a neutral alumina column.
[0051] The unsaturated diester silane monomers in the present invention can be prepared by reacting unsaturated di(chloromethyl)silane with corresponding acid anhydride or acid under alkaline conditions using existing technology, or can be directly used by purchasing from outside.
[0052] In the present invention, the specific surface area of the prepared organic polymer carrier is tested by Nova 2000e using the BET nitrogen adsorption method, and the specific surface area of the carrier prepared by the present invention is controlled to be greater than 100m 2 / g, 100-600m 2 / g, and the pore volume is greater than 0.2ml / g.
[0053] The viscosity average molecular weight of the ultra-high molecular weight polyethylene prepared by the present invention is measured by the method in ASTM D4020. The polymer viscosity is tested by an Ubbelohde viscometer, the solvent is decalin, and the test temperature is 135°C. The polymer viscosity average molecular weight Mη can be obtained by calculating the intrinsic viscosity η of the polymer, using the formula Mη=5.37×10 4 [η] 1.37, the polymer weight average molecular weight Mw can be calculated by Margolis formula Mw = 5.37 × 10 4 [η]1.49 is calculated.
[0054] The internal electron donor content can be determined by extraction and gas chromatography.
[0055] Treatment of comonomers: Before using divinylbenzene, the inhibitor was removed with 10% NaOH solution, then washed with deionized water for 3 times, and dried with anhydrous magnesium sulfate before use.
[0056] Preparation of unsaturated diester silane monomers
[0057] Preparation Example 1
[0058] This preparation example provides a vinylmethylbis(methyl acetate)silane (or vinylmethylbis(acetoxymethyl)silane) monomer, which is prepared by the following steps:
[0059] Vinylmethylbis(methyl acetate)silane compound can be prepared by reacting vinylmethylbis(chloromethyl)silane with acetic anhydride at 40-60°C and normal pressure to obtain a crude product, and then distilling under reduced pressure to obtain vinylmethylbis(methyl acetate)silane. Specifically, 6.0g of acetic anhydride, 12g of vinylmethylbis(chloromethyl)silane and 80g of N,N-dimethylformamide (DMF) solvent are added to a 250ml reactor, and then 12g of anhydrous K2CO3 is added. The crude product is esterified at 60°C and normal pressure, filtered, and distilled under reduced pressure to obtain vinylmethylbis(methyl acetate)silane with a yield of 89%. This preparation method is only for illustration and is not intended to limit the preparation method of unsaturated diester silane. Other monomers can be prepared by similar methods or directly purchased.
[0060] Preparation Example 2
[0061] This preparation example provides allylmethylbis(methylisobutyrate)silane monomer, which is prepared by the following steps:
[0062] Allylmethylbis(methylisobutyrate)silane compound can be prepared by reacting allylmethylbis(chloromethyl)silane with isobutyric acid at 40-60° C. and normal pressure to obtain a crude product, and then distilling under reduced pressure to obtain allylmethylbis(methylisobutyrate)silane. Specifically, 6.0 g of isobutyric acid, 11.2 g of vinylmethylbis(chloromethyl)silane and 80 g of N,N-dimethylformamide (DMF) solvent are added into a 250 ml reactor, and then 12 g of anhydrous K2CO3 is added. The crude product is esterified at 60° C. and normal pressure, and then filtered and distilled under reduced pressure to obtain allylmethylbis(methylisobutyrate)silane with a yield of 85%.
[0063] Preparation Example 3
[0064] This preparation example provides an allylethoxydi(methylbenzoate)silane monomer, which is prepared by the following steps:
[0065] Allylethoxybis(methylbenzoate)silane compound can be prepared by reacting allylethoxybis(chloromethyl)silane with benzoic anhydride at 40-60° C. and normal pressure to obtain a crude product, and then distilling under reduced pressure to obtain allylethoxybis(methylbenzoate)silane. Specifically, 6.0 g of benzoic anhydride, 11.2 g of vinylmethylbis(chloromethyl)silane and 80 g of N,N-dimethylformamide (DMF) solvent are added into a 250 ml reactor, and then 12 g of anhydrous K2CO3 is added. The crude product is esterified at 60° C. and normal pressure, and then filtered and distilled under reduced pressure to obtain allylethoxybis(methylbenzoate)silane with a yield of 91%.
[0066] Preparation Example 4
[0067] This preparation example provides 1-butene-4-yl isopropyl di(methylbenzoate)silane monomer, which is prepared by the following steps:
[0068] 1-Butene-4-yl isopropyl di(methyl benzoate)silane compound can be prepared by 1-butene-4-yl isopropyl di(chloromethyl)silane and benzoic anhydride at 40-60° C. and normal pressure to obtain a crude product, and then reduced pressure distillation to obtain 1-butene-4-yl isopropyl di(methyl benzoate)silane. Specifically, 6.0 g of benzoic anhydride and 11.5 g of 1-butene-4-yl isopropyl di(chloromethyl)silane and 80 g of N,N-dimethylformamide (DMF) solvent are added into a 250 ml reactor, and then 12 g of anhydrous K2CO3 is added, and esterification is carried out at 60° C. and normal pressure to obtain a crude product, which is then filtered and distilled under reduced pressure to obtain 1-butene-4-yl isopropyl di(methyl benzoate)silane with a yield of 83%.
[0069] Example 1
[0070] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0071] (1) Preparation of porous organic polymer carrier:
[0072] In a 250ml glass reactor, add 130ml ethyl acetate, then add 5.0g divinylbenzene (Aladdin reagent, 55%) and 2.0g vinylmethylbis(methyl acetate)silane, stir at room temperature for 5min, then add 3% monomer weight of polyvinyl alcohol PVA (PVA, degree of polymerization 1750), stir at 45°C for 1h to completely dissolve the stabilizer, add 2.0% monomer weight of azobisisobutyronitrile (AIBN), heat to 70°C, react for 3 hours, then raise the temperature to 80°C, react for 7 hours, stir at 350 rpm, filter, wash 3 times with ethyl acetate, 100ml each time, filter, dry, and obtain 3.8g of free-flowing porous organic polymer carrier POP-1. The specific surface area of the carrier is 238m 2 / g;
[0073] (2) Catalyst preparation:
[0074] In a 250ml glass reactor, add 2.0g of the carrier POP-1 prepared by using the above-mentioned vinylmethylbis(methyl acetate)silane functional monomer, add 100ml of toluene, stir, then add 15ml of 3M methylmagnesium chloride Grignard reagent at room temperature (25°C, the same below), stir for 2 hours, filter, wash twice with toluene, then add 50ml of toluene, add 50ml of TiCl4 dropwise at room temperature, heat to 80°C and react for 2 hours, filter, wash with toluene and hexane 3 times each, and obtain free-flowing catalyst particles after drying, which are recorded as Cat-1. The Mg content of catalyst Cat-1 is 4.2%, the titanium content is 3.2%, and the organic polymer carrier content is 71%.
[0075] Example 2
[0076] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0077] Catalyst preparation: In a 250 ml glass reactor, add 2.0 g of the carrier POP-1 prepared using the above-mentioned vinylmethylbis(methyl acetate)silane functional monomer, add 100 ml of toluene, stir, then add 10 ml of 3M methylmagnesium chloride Grignard reagent at room temperature, stir for 2 hours, filter, wash twice with toluene, then add 50 ml of toluene, add 30 ml of TiCl4 dropwise at room temperature, heat to 60° C. and react for 2 hours, filter, wash with toluene and hexane 3 times each, and obtain free-flowing catalyst particles after drying, which are recorded as Cat-2. The Mg content of catalyst Cat-2 is 2.8%, the titanium content is 2.5%, and the organic polymer carrier content is 81%.
[0078] Example 3
[0079] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0080] (1) Preparation of porous organic polymer carrier:
[0081] In a 250ml glass reactor, add 130ml butyl acetate, then add 6.0g divinylbenzene (Aladdin reagent, 50%) and 3.0g vinylmethyldi(methyl acetate)silane, stir at room temperature for 5min, then add 3% monomer mass of block copolymer of polyethylene oxide and polypropylene oxide F127, stir at 45°C for 1h to completely dissolve the stabilizer, add 2.0% monomer mass of dibenzoyl peroxide BPO, heat to 70°C, react for 3 hours, then raise the temperature to 80°C, react for 8 hours, stir at 450 rpm, filter, wash 3 times with 100ml ethyl acetate, filter and dry to obtain 6.3g of free-flowing porous organic polymer carrier POP-2. The carrier has a specific surface area of 378m 2 / g;
[0082] (2) Catalyst preparation:
[0083] In a 250ml glass reactor, add 2.0g of the carrier POP-2 prepared by using the above-mentioned vinylmethylbis(methyl acetate)silane functional monomer, add 100ml of toluene, stir, then add 12ml of 3M methylmagnesium chloride Grignard reagent at room temperature, stir for 2 hours, filter, wash twice with toluene, then add 50ml of toluene, add 35ml TiCl4 dropwise at room temperature, heat to 80°C and react for 2 hours, filter, wash with toluene and hexane 3 times each, and obtain free-flowing catalyst particles after drying, which are recorded as Cat-3. The Mg content of catalyst Cat-3 is 3.2%, the titanium content is 2.8%, and the organic polymer carrier content is 73%.
[0084] Example 4
[0085] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0086] (1) Preparation of porous organic polymer carrier: In a 250 ml glass reactor, add 120 ml of ethyl acetate, then add 5.0 g of divinylbenzene (Aladdin reagent, 55%) and 2.0 g of allylmethyldi(methylisobutyrate)silane, stir at room temperature for 5 min, then add 2% monomer weight of polyvinyl alcohol PVA (PVA, degree of polymerization 1750), stir at 45°C for 1 h to completely dissolve the stabilizer, add 2.0% monomer weight of AIBN, heat to 70°C, react for 3 hours, then heat to 80°C, react for 7 hours, stir at 450 rpm, filter, wash 3 times with ethyl acetate, 100 ml each time, filter, dry, and obtain 3.8 g of free-flowing porous organic polymer carrier POP-3. The specific surface area of the carrier is 245 m 2 / g;
[0087] (2) Preparation of ZN catalyst:
[0088] In a 250ml glass reactor, 2g of the carrier POP-3 prepared from the functional monomer of allylmethylbis(methylisobutyrate)silane was added, 100ml of toluene was added, stirred, then 10ml of 3M methylmagnesium chloride Grignard reagent was added at room temperature, stirred for 2 hours, filtered, washed twice with toluene, then 50ml of toluene was added, 30ml of TiCl was added dropwise at room temperature, the temperature was raised to 60°C and the reaction was performed for 2 hours, filtered after completion of the reaction, then 50ml of toluene was added dropwise, 30ml of TiCl was added dropwise at room temperature, the reaction was performed at 80°C for 1 hour, filtered, washed 3 times with toluene and hexane respectively, and dried to obtain free-flowing catalyst particles, which were designated as Cat-4. The catalyst Cat-4 had a Mg content of 2.7%, a titanium content of 2.4%, and an organic polymer carrier content of 78%.
[0089] Example 5
[0090] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0091] Preparation of ZN catalyst: In a 250ml glass reactor, add 2g of the carrier POP-3 prepared from the functional monomer of allylmethylbis(methylisobutyrate)silane, add 100ml of toluene, stir, then add 15ml of 3M methylmagnesium chloride Grignard reagent at 5°C, stir for 2 hours, filter, wash twice with toluene, then add 50ml of toluene, add 40mlTiCl4 dropwise at room temperature, react for 1 hour, heat to 80°C, react for 2 hours, filter after completion of the reaction, wash 3 times with toluene and hexane respectively, and obtain free-flowing catalyst particles after drying, recorded as Cat-5. The Mg content of catalyst Cat-5 is 4.0%, the titanium content is 4.2%, and the organic polymer carrier content is 68%.
[0092] Example 6
[0093] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0094] Preparation of ZN catalyst: In a 250ml glass reactor, 2g of the above-mentioned carrier POP-3 prepared from the functional monomer of allylmethyldi(methylisobutyrate)silane was added, 100ml of toluene was added, stirred, then 15ml of 3M methylmagnesium chloride Grignard reagent was added at 5°C, stirred for 2 hours, filtered, washed twice with toluene, then 50ml of toluene was added, 40ml of TiCl was added dropwise at room temperature, reacted for 1 hour, warmed to 80°C, then 0.21g of diisobutyl phthalate (DIBP) internal electron donor was added, reacted for 2 hours, after completion of the reaction, filtered, then 50ml of toluene and 30ml of TiCl were added again, reacted for 2 hours at 80°C, filtered after completion of the reaction, washed 3 times with toluene and hexane, and dried to obtain free-flowing catalyst particles, designated as Cat-6, wherein the Mg content of the catalyst Cat-6 was 4.0%, the titanium content was 3.8%, the electron donor content in DIBP was 3.1%, and the organic polymer carrier content was 73%.
[0095] Example 7
[0096] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0097] Preparation of ZN catalyst: In a 250ml glass reactor, 2g of the carrier POP-3 prepared from the functional monomer of allylmethylbis(methylisobutyrate)silane was added, 100ml of toluene was added, stirred, and then 10ml of 3M benzylmagnesium chloride Grignard reagent was added at 35°C, stirred for 2 hours, filtered, washed twice with toluene, then warmed to 50°C, 40ml of TiCl was added dropwise, reacted for 2 hours, then warmed to 80°C, 0.15g of 3-methyl-5-tert-butyl-1,2-benzenediol dibenzoate was added, reacted for 3 hours, after completion of the reaction, filtered, 50ml of toluene and 30ml of TiCl were added again, reacted at 80°C for 2 hours, filtered after completion of the reaction, washed 3 times with toluene and hexane, and dried to obtain free-flowing catalyst particles, denoted as Cat-7, the Mg content of the catalyst Cat-7 being 2.8%, the titanium content being 3.2%, the internal electron donor content being 2.8%, and the organic polymer carrier content being 69%.
[0098] Example 8
[0099] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0100] (1) Preparation of porous organic polymer carrier:
[0101] In a 250ml glass reactor, add 120ml butyl acetate, then add 5.0g divinylbenzene (Aladdin reagent, 55%) and 2.5g allylethoxybis(methylbenzoate)silane, stir at room temperature for 5min, then add 5% monomer mass of block copolymer of polyethylene oxide and polypropylene oxide F127, stir at 45℃ for 1h to completely dissolve the stabilizer, add 2.0% monomer mass of AIBN, heat to 70℃, react for 3 hours, then raise the temperature to 80℃, react for 7 hours, stir at 550 rpm, filter, wash 3 times with ethyl acetate, 100ml each time, filter, dry to obtain 4.5g free-flowing porous organic polymer carrier POP-4. The carrier specific surface area is 378m 2 / g;
[0102] (2) Preparation of ZN catalyst:
[0103] In a 250ml glass reactor, 2g of the carrier POP-4 prepared from the functional monomer of allylethoxybis(methylbenzoate)silane was added, 100ml of toluene was added, stirred, then 12ml of 3M methylmagnesium chloride Grignard reagent was added at room temperature, stirred for 2 hours, filtered, washed twice with toluene, then 50ml of toluene was added, 50ml of TiCl was added dropwise at room temperature, the temperature was raised to 60°C and the reaction was performed for 2 hours, the reaction was completed and filtered, then 50ml of toluene was added dropwise, 30ml of TiCl was added dropwise at room temperature and the reaction was performed at 80°C for 1 hour, the catalyst was filtered and washed 3 times with toluene and hexane, and free-flowing catalyst particles were obtained after drying, which were designated as Cat-8. The Mg content of the catalyst Cat-8 was 3.2%, the titanium content was 3.4%, and the organic polymer carrier content was 72%.
[0104] Example 9
[0105] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0106] Preparation of ZN catalyst: In a 250ml glass reactor, add 2.0g of the carrier POP-4 prepared from the functional monomer of allylethoxybis(methylbenzoate)silane, add 80ml of toluene, stir, then add 8ml of 3M methylmagnesium chloride Grignard reagent at 35°C, stir for 2 hours, filter, wash twice with toluene, then heat to 50°C, add 30ml TiCl4 dropwise, react for 2 hours, then heat to 80°C, after completion of the reaction, filter, wash 3 times with toluene and hexane respectively, and obtain free-flowing catalyst particles after drying, recorded as Cat-9, the Mg content of catalyst Cat-9 is 2.1%, the titanium content is 2.2%, and the organic polymer carrier content is 82%.
[0107] Example 10
[0108] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0109] Preparation of ZN catalyst: In a 250 ml glass reactor, 2.0 g of the carrier POP-4 prepared from the functional monomer of allylethoxybis(methylbenzoate)silane was added, 80 ml of toluene was added, stirred, and then 15 ml of 3M di-n-butylmagnesium was added at room temperature, stirred for 3 hours, filtered, washed twice with toluene, then heated to 50° C., 40 ml of TiCl4 was added dropwise, reacted for 2 hours, then heated to 80° C., 0.25 g of DIBP internal electron donor was added, reacted for 3 hours, after completion of the reaction, filtered, washed 3 times with toluene and hexane respectively, and dried to obtain free-flowing catalyst particles, recorded as Cat-10. The Mg content of the catalyst Cat-10 was 2.7%, the titanium content was 2.5%, the internal electron donor content was 3.2%, and the organic polymer carrier content was 77%.
[0110] Embodiment 11
[0111] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0112] (1) Preparation of porous organic polymer carrier:
[0113] In a 250ml glass reactor, add 130ml butyl acetate, then add 5.0g divinylbenzene (Aladdin reagent, 55%) and 3.0g allylethoxybis(methylbenzoate)silane, and 2.0g 4-chloromethylstyrene, stir at room temperature for 5min, then add 5% monomer weight of block copolymer of polyethylene oxide and polypropylene oxide F127, stir at 45℃ for 1h to completely dissolve the stabilizer, add 2.0% monomer weight of AIBN, heat to 70℃, react for 3 hours, then heat to 80℃, react for 10 hours, stir at 450 rpm, filter, wash 3 times with ethyl acetate, 100ml each time, filter, dry, and obtain 7.6g free-flowing porous organic polymer carrier POP-5. The carrier has a specific surface area of 325m 2 / g;
[0114] (2) Preparation of ZN catalyst:
[0115] In a 250ml glass reactor, 3g of the carrier POP-5 prepared from 3.0g of allylethoxybis(methylbenzoate)silane and the third monomer 4-chloromethylstyrene was added, 100ml of toluene was added, stirred, and then 15ml of 3M methylmagnesium chloride Grignard reagent was added at 20°C, stirred for 2 hours, filtered, washed twice with toluene, then heated to 50°C, 50ml of TiCl4 was added dropwise, then heated to 80°C, reacted for 2 hours, and after completion of the reaction, filtered, washed 3 times with toluene and hexane respectively, and dried to obtain free-flowing catalyst particles, recorded as Cat-11. The catalyst Cat-11 has a Mg content of 2.7%, a titanium content of 2.8%, and an organic polymer carrier content of 76%.
[0116] Example 12
[0117] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0118] Preparation of ZN catalyst: In a 250 ml glass reactor, 3 g of the carrier POP-5 prepared from 3.0 g of allylethoxybis(methylbenzoate)silane and the third monomer 4-chloromethylstyrene was added, 100 ml of toluene was added, stirred, and then 15 ml of 3M methylmagnesium chloride Grignard reagent was added at 0° C., stirred for 2 hours, filtered, washed twice with toluene, then heated to 50° C., 50 ml of TiCl4 was added dropwise, reacted for 2 hours, then heated to 80° C., 0.25 g of 9,9-dimethoxyfluorene internal electron donor was added, reacted for 3 hours, after completion of the reaction, filtered, washed 3 times each with toluene and hexane, and dried to obtain free-flowing catalyst particles, recorded as Cat-12, the Mg content of the catalyst Cat-12 was 2.4%, the titanium content was 2.4%, the electron donor content was 2.1%, and the organic polymer carrier content was 73%.
[0119] Example 13
[0120] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0121] (1) Preparation of porous organic polymer carrier:
[0122] In a 250ml glass reactor, add 120ml butyl acetate, then add 5.0g divinylbenzene (Aladdin reagent, 55%) and 1.8g 1-butene-4-yl isopropyl di(methyl benzoate) silane, stir at room temperature for 5min, then add 3% monomer mass of block copolymer of polyethylene oxide and polypropylene oxide F127, stir at 45℃ for 1h to completely dissolve the stabilizer, add 2.0% monomer mass of AIBN, heat to 70℃, react for 3 hours, then raise the temperature to 80℃, react for 10 hours, stir at 550 rpm, filter, wash 3 times with ethyl acetate, 100ml each time, filter, dry to obtain 4.1g free-flowing porous organic polymer carrier POP-6. The carrier specific surface area is 248m 2 / g;
[0123] (2) Preparation of ZN catalyst:
[0124] In a 250ml glass reactor, 2.0g of the carrier POP-6 prepared from the functional monomer of 1-butene-4-ylisopropyldi(methylbenzoate)silane was added, 100ml of toluene was added, stirred, then 12ml of 3M methylmagnesium chloride Grignard reagent was added at room temperature, stirred for 2 hours, filtered, washed twice with toluene, then 50ml of toluene was added, 30ml of TiCl4 was added dropwise at room temperature, the temperature was raised to 60°C and reacted for 2 hours, filtered after completion of the reaction, then 50ml of toluene was added, 30ml of TiCl4 was added dropwise at room temperature and reacted at 80°C for 1 hour, filtered, washed 3 times with toluene and hexane respectively, and dried to obtain free-flowing catalyst particles, recorded as Cat-13. The catalyst Cat-13 has a Mg content of 2.8%, a titanium content of 2.1%, and an organic polymer carrier content of 79%.
[0125] Embodiment 14
[0126] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0127] Preparation of ZN catalyst: In a 250ml glass reactor, 2g of the carrier POP-6 prepared from the functional monomer of 1-butene-4-yl isopropyl di(methyl benzoate) silane was added, 100ml of toluene was added, stirred, then 15ml of 3M methyl magnesium chloride Grignard reagent was added at room temperature, stirred for 2 hours, filtered, washed twice with toluene, then 50ml of toluene was added, 50ml of TiCl4 was added dropwise at room temperature, the temperature was raised to 60°C and reacted for 2 hours, filtered after completion of the reaction, then 50ml of toluene was added dropwise, 30ml of TiCl4 was added dropwise at room temperature and reacted at 80°C for 1 hour, filtered, washed 3 times with toluene and hexane respectively, and dried to obtain free-flowing catalyst particles, recorded as Cat-14, the Mg content of the catalyst Cat-14 was 4.5%, the titanium content was 4.2%, and the organic polymer carrier content was 67%.
[0128] Embodiment 15
[0129] This embodiment provides a ZN catalyst, which is prepared by the following steps:
[0130] Preparation of ZN catalyst: In a 250ml glass reactor, 3g of the carrier POP-6 prepared from the functional monomer of 1-butene-4-yl isopropyl di(methyl benzoate) silane was added, 100ml of toluene was added, stirred, and then 15ml of 3M methyl magnesium chloride Grignard reagent was added at 20°C, stirred for 2 hours, filtered, washed twice with toluene, then heated to 50°C, 40ml of TiCl was added dropwise, reacted for 2 hours, then heated to 80°C, 0.25g of DIBP internal electron donor was added, reacted for 3 hours, after the reaction was completed, filtered, and then 100ml of TiCl was added and reacted at 80°C for 1 hour. After filtering, toluene and hexane were used to wash 3 times each, and free-flowing catalyst particles were obtained after drying, which were recorded as Cat-15. The Mg content of the catalyst Cat-15 was 2.8%, the titanium content was 3.2%, the electron donor content was 2.9%, and the organic polymer carrier content was 71%.
[0131] Ethylene polymerization
[0132] In a polymerization reactor, ethylene slurry polymerization is carried out using the catalyst prepared above to prepare UHMWPE.
[0133] Ethylene homopolymerization process: 2.0 liters of dry hexane are added to a 5-liter stainless steel autoclave that has been replaced with nitrogen and dried, and then a certain amount of triethylaluminum TEA (1.0 mol / L) is added, stirred, and then 50 mg of the above-mentioned catalyst is added, and ethylene is introduced to keep the internal pressure of the reactor at 0.6-1.0 MPa. At a specific polymerization temperature (60-80°C), the polymerization is carried out for 1 hour under stirring at 600 rpm, the reaction is terminated, cooled to room temperature, and dried to obtain a polyethylene product.
[0134] Test Example 1
[0135] 2.0 liters of dry hexane were added to a 5-liter stainless steel autoclave that had been replaced with nitrogen and dried, and then 5 ml of triethylaluminum TEA (1.0 mol / L) was added. The stirring speed was 450 rpm, and then 50 mg of catalyst Cat-1 was added. Ethylene was introduced to keep the internal pressure of the reactor at 1.0 MPa (10 bar). The temperature was raised to 70° C. and the polymerization was carried out under stirring at 600 rpm for 1 hour. After the reaction was completed, the reaction was terminated, cooled to room temperature, and dried to obtain 528 g of UHMWPE-1 product with a catalyst activity of 10560 gPE / gcat.h, or 1580 kgPE / molTi.bar.h. The results are shown in Table 1.
[0136] Test Example 2-15
[0137] The ethylene polymerization conditions in Test Example 2-15 are the same as those in Test Example 1 except for the addition of different catalysts. The catalysts used in Test Examples 2-15 are Cat-2 to Cat-15, respectively. The polymerization results are shown in Table 1.
[0138] Test Example 16
[0139] 2.0 liters of dry hexane were added to a 5-liter stainless steel autoclave that had been replaced with nitrogen and dried, and then 5 ml of triethylaluminum TEA (1.0 mol / L) was added. The stirring speed was 450 rpm, and then 50 mg of catalyst Cat-8 was added. Ethylene was introduced to keep the internal pressure of the reactor at 1.0 MPa. The temperature was raised to 60°C and the polymerization was carried out under stirring at 600 rpm for 1 hour. After the reaction was completed, the reaction was terminated, cooled to room temperature, and dried to obtain ultra-high molecular weight polyethylene powder particles. The results are shown in Table 1.
[0140] Test Example 17
[0141] 2.0 liters of dry hexane were added to a 5-liter stainless steel autoclave that had been replaced with nitrogen and dried, and then 8 milliliters of triethylaluminum TEA (1.0 mol / liter) was added. The stirring speed was 450 rpm, and then 50 mg of catalyst Cat-8 was added. Ethylene was introduced to keep the internal pressure of the reactor at 0.8 MPa, and 0.20 g of hydrogen was added. The temperature was raised to 70°C, and the polymerization was carried out under stirring at 600 rpm for 1 hour. After the reaction was completed, the reaction was terminated, cooled to room temperature, and dried to obtain UHMWPE particles. The results are shown in Table 1.
[0142] Test Example 18
[0143] 2.0 liters of dry hexane were added to a 5-liter stainless steel autoclave that had been replaced with nitrogen and dried, and then 8 ml of triethylaluminum TEA (1.0 mol / L) was added. The stirring speed was 450 rpm, and then 350 mg of catalyst Cat-1 was added. Ethylene was introduced to keep the internal pressure of the reactor at 1.0 MPa. The temperature was raised to 80°C and the polymerization was carried out under stirring at 600 rpm for 1 hour. After the reaction was completed, the reaction was terminated, cooled to room temperature, and dried to obtain UHMWPE particles. The results are shown in Table 1.
[0144] Test Case 19
[0145] 2.0 liters of dry hexane were added to a 5-liter stainless steel autoclave that had been replaced with nitrogen and dried, and then 5 ml of triethylaluminum TEA (1.0 mol / L) was added. The stirring speed was 450 rpm, and then 350 mg of catalyst Cat-1 was added. Ethylene was introduced to keep the internal pressure of the reactor at 0.6 MPa. The temperature was raised to 60°C and the polymerization was carried out under stirring at 600 rpm for 1 hour. After the reaction was completed, the reaction was terminated, cooled to room temperature, and dried to obtain UHMWPE particles. The results are shown in Table 1.
[0146] Test Example 20
[0147] 2.0 liters of dry hexane were added to a 5-liter stainless steel autoclave that had been replaced with nitrogen and dried, and then 10 ml of triethylaluminum TEA (1.0 mol / L) was added. The stirring speed was 450 rpm, and then 350 mg of catalyst Cat-1 was added. Ethylene was introduced to keep the internal pressure of the reactor at 1.0 MPa. The temperature was raised to 80°C and the polymerization was carried out under stirring at 600 rpm for 1 hour. After the reaction was completed, the reaction was terminated, cooled to room temperature, and dried to obtain UHMWPE particles. The results are shown in Table 1.
[0148] Table 1 Aggregation results
[0149]
[0150]
[0151] The polymerization conditions in comparative test example 1 were: 1L polymerization reactor, 500ml hexane, cat: 43mg, Al / Ti=300 (molar ratio), polymerization pressure 5bar, polymerization time 2 hours. The titanium content of the catalyst was estimated to be 1.64mmol / g.
[0152] The polymerization conditions in comparative test example 2 are: 100 ml heptane, cat: 50 mg, Al / Ti=300 (molar ratio), polymerization pressure 1 bar, polymerization time 1 hour. The titanium content in the ZN3 catalyst is 2.5%.
[0153] The polymerization conditions in comparative test example 3 were: 1L polymerization reactor, 400ml isobutane, cat: 18mg, Al / Ti=190 (molar ratio), polymerization pressure 40bar, polymerization time 3 hours, and catalyst titanium content 45μmol Ti / g cat.
[0154] The data in the comparative test cases are all from the corresponding literature 1, 2, 3, among which:
[0155] Reference 1: “Porous polyethylene spheres with nanofiber structure from Ziegler-Natta catalyst supported on porous polymer particles” in Polymer (2011; Vol. 52, pp. 602-605);
[0156] Reference 2: “Ethylene polymerization on polymer supported Ziegler-Natta catalyst” in J. Polym. Res. (2012; 19: 9892, pp. 1-13);
[0157] Document 3: "UltrahighMolecular Weight Polyethylene Produced by a Bis(phenoxy-imine)TitaniumComplex Supported on Latex Particles" in Journal of Polymer Science: Part A: Polymer Chemistry (2006; pp. 3103-3113).
[0158] As can be seen from Table 1, the porous organic polymer carrier-supported ZN catalyst containing diester silane functional monomers of the present invention is used for ethylene homopolymerization, and the weight average molecular weight of the polyethylene obtained is between 500,000 and 12 million, and the viscosity average molecular weight can reach more than 7 million, which is higher than the FI-Ti catalyst system supported by the organic carrier reported in Document 3. The organic carrier-supported ZN catalyst containing diester silane functional monomers of the present invention has good polymerization activity and good hydrogen adjustment sensitivity, and the polymerization activity is between 1200-6300kgPE / molTi.bar.h, reaching the activity level of commercial inorganic carrier-supported ZN ultra-high molecular weight polyethylene catalysts.
Claims
1. An organic polymer carrier obtained by copolymerizing monomers including divinylbenzene and unsaturated diester silane monomers; in, The unsaturated diester silane monomer has a structure shown in Formula I: In formula I, R1, R2, and R3 are each independently selected from hydrogen, chlorine, bromine, C1-C6 straight-chain alkyl and derivatives thereof, C1-C6 branched-chain alkyl and derivatives thereof, cycloalkyl and derivatives thereof, and aromatic groups and derivatives thereof; x is 0-6; R4 is selected from hydrogen, C1-C8 straight-chain alkyl and derivatives thereof, C1-C8 branched-chain alkyl and derivatives thereof, cycloalkyl and derivatives thereof, and aromatic groups and derivatives thereof; R5 and R6 are each independently selected from hydrogen, C1-C8 straight-chain hydrocarbon groups and derivatives thereof, C1-C8 branched-chain hydrocarbon groups and derivatives thereof, cycloalkyl and derivatives thereof, and aromatic groups and derivatives thereof.
2. The organic polymer carrier according to claim 1, wherein In formula I, R1, R2, and R3 are each independently selected from hydrogen, chlorine, bromine, methyl, and ethyl; R4 is selected from methyl, ethyl, isopropyl, n-butyl, isobutyl, phenyl, phenoxy, methoxy, ethoxy; R5 and R6 are each independently selected from hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, n-pentyl, n-heptyl, phenyl, cyclohexyl, isohexyl, 2-ethylpentyl, 2-ethylbutyl; x is 0 or 1.
3. The organic polymer carrier according to claim 1, wherein The unsaturated diester silane monomer is selected from vinylmethylbis(methyl formate)silane, vinylmethylbis(methyl acetate)silane, vinylmethylbis(methyl propionate)silane, vinylmethylbis(methyl butyrate)silane, vinylmethylbis(methyl isobutyrate)silane, vinylmethylbis(methyl valerate)silane, vinylmethylbis(methyl hexanoate)silane, vinylmethylbis(methyl octanoate)silane, vinylmethylbis(methyl 2-methylhexanoate)silane, vinylmethylbis(methyl 2-ethylhexanoate)silane, vinylmethylbis(methyl 2-ethylhexanoate)silane, 2-ethylpentanoate) silane, vinylmethylbis(methylbenzoate)silane, vinylmethylbis(methylcyclohexanecarboxylate)silane, vinylethylbis(methylacetate)silane, vinylphenylbis(methylacetate)silane, vinyl-n-butylbis(methylacetate)silane, vinylisobutylbis(methylacetate)silane, vinylisopropylbis(methylacetate)silane, vinylethoxybis(methylacetate)silane, allylmethylbis(methylacetate)silane, allylmethylbis(methylpropionate)silane, allylmethylbis(methylbutyrate)silane silane, allylmethylbis(methyl isobutyrate)silane, allylmethylbis(methyl pentanoate)silane, allylmethylbis(methyl hexanoate)silane, allylmethylbis(methyl octanoate)silane, allylmethylbis(methyl 2-methylhexanoate)silane, allylmethylbis(methyl 2-ethylhexanoate)silane, allylmethylbis(methyl 2-ethylpentanoate)silane, allylmethylbis(methyl benzoate)silane, allylmethylbis(methyl cyclohexane)silane, allylethylbis(methyl acetate)silane, allylphenylbis(methyl acetate)silane alkane, allyl n-butylbis(methyl acetate)silane, allyl isobutylbis(methyl acetate)silane, allyl isopropylbis(methyl acetate)silane, allyl methoxybis(methyl acetate)silane, allyl ethoxybis(methyl acetate)silane, allyl ethoxybis(methyl benzoate)silane, 1-butenyl ethoxybis(methyl acetate)silane, 1-buten-4-yl isopropylbis(methyl benzoate)silane, allyl phenoxybis(methyl acetate)silane, 1-chloroallyl ethoxybis(methyl acetate)silane or a combination of two or more thereof.
4. The organic polymer carrier according to claim 1, wherein Calculated based on the mass of the organic polymer carrier being 100%, the mass fraction of the unsaturated diester-based silane monomer is 10-60%.
5. The method for preparing the organic polymer carrier according to any one of claims 1 to 4, comprising the following steps: The organic polymer carrier is prepared by copolymerizing the monomers including the divinylbenzene, the unsaturated diester silane monomer and the additional monomer as raw materials; The mass ratio of the additional monomer to divinylbenzene is 0-1:1; the mass ratio of the unsaturated diester silane monomer to divinylbenzene is 0.2-2:1; Preferably, the organic polymer carrier is prepared by dispersion polymerization, suspension polymerization or emulsion polymerization; the dispersion polymerization method comprises the following steps: adding divinylbenzene, unsaturated diester silane monomers, additional monomers into a dispersion solvent, and then adding a stabilizer and an initiator, stirring and dispersing, and reacting at 50-80°C for 5-12 hours to obtain the organic polymer carrier.
6. The preparation method according to claim 5, wherein: The additional monomers include one or a combination of two or more of styrene, alkyl-substituted styrene, chloromethyl-substituted styrene, methacrylic acid, methacrylate, and hydroxyalkyl methacrylate.
7. The preparation method according to claim 5, wherein: The dispersing solvent includes a fatty acid ester solvent; Preferably, the fatty acid ester solvent includes ethyl acetate and / or butyl acetate.
8. The preparation method according to claim 5, wherein: The mass ratio of the total amount of monomer added to the dispersing solvent is 1:5-20.
9. The preparation method according to claim 5, wherein: The stabilizer is polyvinyl alcohol and / or polypropylene oxide-polyethylene oxide copolymer; Preferably, the weight average molecular weight of the stabilizer is 1000-100000; Preferably, the mass ratio of the amount of the stabilizer added to the total amount of the monomers added is 0.5-5:
100.
10. The preparation method according to claim 5, wherein: The initiator is azobisisobutyronitrile and / or dibenzoyl peroxide; Preferably, the mass ratio of the amount of the initiator added to the total amount of the monomers added is 0.5-5:
100.
11. The preparation method according to claim 5, wherein: The divinylbenzene is pretreated divinylbenzene, and the pretreatment is to remove the polymerization inhibitor.
12. A ZN catalyst, wherein the raw material composition comprises 60-85wt% of an organic polymer carrier, 1-6wt% of a magnesium compound calculated as magnesium element, 1-6wt% of a titanium compound calculated as titanium element, and 0-5wt% of an internal electron donor, based on the mass of the ZN catalyst being 100%; The organic polymer carrier is the organic polymer carrier according to any one of claims 1 to 4; Preferably, the content of the organic polymer carrier is 65-80wt%, the content of magnesium is 2-5wt%, and the content of titanium is 2-5wt%.
13. The ZN catalyst according to claim 12, wherein The magnesium compound is R n MgX (2-n) , n is 0, 1 or 2; R is selected from C1-C8 alkyl and its derivatives, aryl and its derivatives, alkoxy and its derivatives, and X is fluorine, chlorine, bromine or iodine; Preferably, R is selected from methyl, ethyl, propyl, butyl, alkoxy, phenyl, and substituted phenyl.
14. The ZN catalyst according to claim 13, wherein The magnesium compound is one or a combination of two or more of an alkyl halogenated magnesium compound, an alkyl magnesium compound, and an alkoxy magnesium halide compound; Preferably, the magnesium compound includes one or a combination of two or more of methylmagnesium chloride, n-butylmagnesium chloride, isobutylmagnesium chloride, tert-butylmagnesium chloride, benzylmagnesium chloride, ethylmagnesium chloride, methylmagnesium bromide, ethylmagnesium bromide, n-butylmagnesium bromide, benzylmagnesium bromide, methylmagnesium iodide, tert-butylmagnesium iodide, benzylmagnesium iodide, n-butylmagnesium iodide, methylmagnesium fluoride, tert-butylmagnesium fluoride, diethylmagnesium, dipropylmagnesium, dibutylmagnesium, and ethoxymagnesium chloride.
15. The ZN catalyst according to claim 12, wherein The titanium compound is titanium tetrachloride.
16. The ZN catalyst according to claim 12, wherein The internal electron donor is one or a combination of two or more of diester compounds, diphenol ester compounds, glycol ester compounds, succinate ester compounds, and diether compounds.
17. The ZN catalyst according to claim 16, wherein The internal electron donor includes one or a combination of two or more of diisobutyl phthalate, di-n-butyl phthalate, 9,9-dimethoxyfluorene, diisobutyl 2,3-diisopropylsuccinate, 3-methyl-5-tert-butyl-1,2-benzenediol dibenzoate, 2-isopropyl-2-isopentyl-1,3-propanediol dibenzyl ester, and 2-isopropyl-2-isopentyl-1,3-propanedimethyl ether.
18. A method for preparing the ZN catalyst according to any one of claims 12 to 17, comprising the following steps: Under anhydrous and oxygen-free conditions, the organic polymer carrier is added to an inert solvent, the magnesium compound is added, and the reaction is carried out at 0°C-50°C for 15-120 minutes. The unreacted magnesium compound is filtered, and then an inert solvent and titanium tetrachloride are added. After reacting at 0°C-80°C for 15-180 minutes, an internal electron donor is added at 20°C-120°C, the reaction is carried out for 15-180 minutes, the reaction is filtered, and finally the ZN catalyst is washed with an inert solvent.
19. A ZN catalyst system, comprising a ZN catalyst and a co-catalyst; in, The ZN catalyst is the ZN catalyst according to any one of claims 12 to 17.
20. The ZN catalyst system according to claim 19, wherein The co-catalyst comprises an alkyl aluminum compound; Preferably, the co-catalyst is triethylaluminum and / or triisobutylaluminum.
21. The ZN catalyst system according to claim 20, wherein The molar ratio of aluminum in the alkyl aluminum compound to titanium in the ZN catalyst is 10-500.
22. Use of the ZN catalyst according to any one of claims 12 to 17 or the ZN catalyst system according to claims 19 to 21 in olefin polymerization.
23. The use according to claim 22, wherein: The olefin polymerization is ethylene homopolymerization.
24. The use according to claim 22, wherein: The olefin polymerization is gas phase polymerization, bulk polymerization or slurry polymerization; Preferably, the reaction temperature of the slurry polymerization is 30-80°C and the reaction pressure is 0.1-2.0Mpa; Preferably, the solvent for the slurry polymerization is C5-C 10 An alkane, more preferably hexane.
Citation Information
Patent Citations
Method for producing ultra-high molecular weight polymers by means of special bridged metallocene catalysts
CN101356199A
Olefin polymerization catalyst and polyethylene with ultralow branching coefficient and ultrahigh molecular weight
CN102030844B
Preparation method of catalyst for compounding ultrahigh molecular weight polyethylene
CN103509140A
Ultrahigh molecular weight polyethylene resin with high impact strength and preparation method thereof
CN106220768A
Ultra-high molecular weight polyethylene, production method and applications
CN107936164A